Simultaneous carbon dioxide capture and utilization using thermal desalination reject brine. (15th September 2015) - Dindi, Abdallah; Quang, Dang Viet; Abu-Zahra, Mohammad R.M.
Highlights: The simultaneous capture and utilization of CO2 with reject brine is feasible. The use of 2 amino 2 methyl propanol (AMP) resulted in high precipitation yield. The proposed amine process is a good replacement for ammonia in the Solvay process. Higher brine concentration improved the CO2 absorption capacity. Abstract: This study evaluated the feasibility of a chemical process which uses desalination brine to convert CO2 into useful sodium bicarbonate. The process is based on the integration of a modified Solvay process with conventional amine based post-combustion carbon dioxide capture for the simultaneous capture and conversion of CO2 into solid bicarbonates. A range of amine solvents were evaluated to select the most suitable solvent for the process. Then the effects of parameters such as temperature, brine concentration and amine concentration on the carbonation step of the process were evaluated. Moreover, different techniques for recovering the amine from the chloride rich solution were proposed and investigated. The sterically hindered amine, 2-amino, 2-methyl propanol (AMP), was found to be the best alcohol amine for the process and the CO2 absorption step was found to be significantly improved at lower temperatures, high brine concentrations and moderate amine concentration. For AMP, the optimum concentration was found to be 30 wt%. Finally, the amine recovery technique tested showed promise and could be optimized further to give better results.